2009
DOI: 10.1186/1471-2148-9-264
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide evolutionary analyses reveal serotype specific patterns of positive selection in selected Salmonella serotypes

Abstract: BackgroundThe bacterium Salmonella enterica includes a diversity of serotypes that cause disease in humans and different animal species. Some Salmonella serotypes show a broad host range, some are host restricted and exclusively associated with one particular host, and some are associated with one particular host species, but able to cause disease in other host species and are thus considered "host adapted". Five Salmonella genome sequences, representing a broad host range serotype (Typhimurium), two host rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
50
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 74 publications
3
50
1
1
Order By: Relevance
“…The specific percentages are for the loci that we studied, which may not be representative of the entire genome, complicating direct comparison of our results with genomic ANI values. Although clusters of closely related sequences can result from causes other than adaptation (52), our observation of Synechococcus ecotypes is one of a growing number of examples of taxa that exhibit numerous extremely closely related sequence clusters corresponding to ecologically distinct populations (10,12,13,22,25,42,43,50,51,58). These clusters occur at a scale of sequence difference well within that formerly used to classify named species.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The specific percentages are for the loci that we studied, which may not be representative of the entire genome, complicating direct comparison of our results with genomic ANI values. Although clusters of closely related sequences can result from causes other than adaptation (52), our observation of Synechococcus ecotypes is one of a growing number of examples of taxa that exhibit numerous extremely closely related sequence clusters corresponding to ecologically distinct populations (10,12,13,22,25,42,43,50,51,58). These clusters occur at a scale of sequence difference well within that formerly used to classify named species.…”
Section: Discussionmentioning
confidence: 75%
“…These analyses have revealed extremely closely related ecotypes in free-living prokaryotes, such as soil Bacillus (12,25), marine Vibrio (22), and acid mine Leptospirillum (13) and Procholorococcus (24,29), as well as among pathogens, including Legionella (10), Escherichia (28,50,51), Mycobacterium (42), Salmonella (43), and Yersinia (58). In all these cases, clusters identified by patterns of sequence diversity (in genes not related to ecological divergence) were confirmed to be ecologically distinct.…”
mentioning
confidence: 86%
“…Unique Bacillus sequence clusters were shown to be associated with desert hillsides having distinct solar exposure patterns and soil textures (8,18). Molecular analyses also have shown closely related, ecologically distinct populations in marine Vibrio (14), acid mine Leptospirillum (9), and multiple pathogens, including Legionella (6), Escherichia (21,29,30), Mycobacterium (25), Salmonella (26), and Yersinia (35). Finally, genetically distinct populations of hot spring Synechococcus have been shown to be associated with different temperatures and vertical distributions (12,24,32).…”
mentioning
confidence: 97%
“…Comparative genomic analysis has demonstrated that unrelated strains of the same Salmonella serovar are typically more similar to each other than to members of other serovars, suggesting serovar-specific evolution (20). Genomic studies of individual serovars have also uncovered an expanding number of open reading frames with single-nucleotide polymorphisms (SNPs) that give rise to allelic variants that may be involved in the adaptation of individual strains to new environments or hosts (1).…”
mentioning
confidence: 99%